Italo Calvino in Mexico: Food and Lovers, Tourists and Cannibals - Biasin, Gian-Paolo (PMLA, 1993)
Italo Calvino's "Sotto il sole giaguaro" ("Under the Jaguar Sun"), a story about the sense of taste, is the culmination of his lifelong research on desire; it presents and analyzes all the primary functions of food, from the satisfaction of a biological need to the possibility of transgression, from the narrative sign to the cognitive tool used to outline the problematic relation among self, others, and the world (or among subject, nature, and history). "Sotto il sole giaguaro" deals with the dialectics of logos, sitos, and eros in an extremely original manner, by foregrounding primary images (like the female protagonist's mouth and the jaguar sun of the title) and by combining the narration of a tourist's journey with a love story and an anthropological inquiry into Aztec cannibalism. In this beautiful and challenging text, gastronomy fuses within itself anthropology and eroticism, while the underlying discourse probes the nature of literature. (G-PB)